ความสัมพันธ์ระหว่างอัตราเงินเฟ้อและการใช้จ่ายของรัฐบาลในจังหวัดเชียงใหม่ - แสงหล้า ปิ่นซ้อน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This is an independent research on a Relationship Between Inflation and Government Expenditure in Chiang Mai Province. The used data is an annual secondary data analysis that relates to Consumer Price Index, Current and Investment Expenditure in Chiang Mai within January 2006 – December 2014. Then the percent of change was calculated as monthly data. The test results of stationary found all data was statistically significant at the 0.01 level indicating that all the data was stationary I(0). The estimate lag found that the appropriate level was 1 Lag.